The Role of Wellness Tourism in the Growth of the Hospitality Industry - Nasiche, Nasiche (Journal of Modern Hospitality, 2024)
Purpose: This study sought to investigate the role of wellness tourism in the growth of the hospitality industry. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to the role of wellness tourism in the growth of the hospitality industry. Preliminary empirical review revealed that wellness tourism significantly boosted the sector by increasing guest satisfaction, revenue, and competitive advantage. It revealed that destinations with developed wellness infrastructure experienced economic benefits, driven by high-spending wellness tourists. The integration of wellness services led to improved operational efficiency and marketing differentiation. The study emphasized the importance of continuous investment in wellness offerings and collaboration between stakeholders to sustain growth. Overall, it concluded that wellness tourism was a key driver of growth and sustainability for the hospitality industry. Unique Contribution to Theory, Practice and Policy: Theory of Planned Behaviour, Maslow's Hierarchy of Needs and Service- Dominant Logic (SDL) may be used to anchor future studies on the role of wellness tourism in the growth of the hospitality industry. The study provided significant insights into how wellness tourism contributed to economic growth, enhanced guest satisfaction, and fostered innovation within the hospitality sector. It integrated theoretical frameworks such as the Theory of Planned Behavior and Maslow's Hierarchy of Needs, highlighted practical recommendations for investing in wellness facilities and leveraging technology, and offered policy suggestions for supportive frameworks and sustainability practices. The study emphasized the importance of long-term strategic planning, innovation, and collaboration in sustaining the growth of wellness tourism and its impact on the hospitality industry. Keywords: Wellness Tourism, Hospitality Industry Growth, Health and Well-being, Tourism Economics, Guest Satisfaction